2017
DOI: 10.1016/j.breast.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the provision and practice of implant-based breast reconstruction in the UK: Results from the iBRA national practice questionnaire

Abstract: IntroductionThe introduction of biological and synthetic meshes has revolutionised the practice of implant-based breast reconstruction (IBBR) but evidence for effectiveness is lacking. The iBRA (implant Breast Reconstruction evAluation) study is a national trainee-led project that aims to explore the practice and outcomes of IBBR to inform the design of a future trial. We report the results of the iBRA National Practice Questionnaire (NPQ) which aimed to comprehensively describe the provision and practice of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
(39 reference statements)
2
34
0
Order By: Relevance
“…18 Implant-based procedures are now the most commonly-performed technique 19,20 and although data from the NMBRA 5 and the National Surgical Quality Improvement Program 21 suggest implant reconstruction may be associated with fewer complications than other techniques, this study suggests that complications following implant-based and autologous reconstruction are broadly comparable. Reasons for this require further evaluation but may reflect the recent adoption of singlestage direct-to-implant mesh-assisted reconstruction in the UK, 22 which may be associated with higher complication rates than the traditional two-stage procedures 23 favoured in the US. 20 Risk factors for complications, including smoking and high BMI are consistent with those previously reported 24,25 and highlight the importance of careful patient selection if post-operative problems are to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…18 Implant-based procedures are now the most commonly-performed technique 19,20 and although data from the NMBRA 5 and the National Surgical Quality Improvement Program 21 suggest implant reconstruction may be associated with fewer complications than other techniques, this study suggests that complications following implant-based and autologous reconstruction are broadly comparable. Reasons for this require further evaluation but may reflect the recent adoption of singlestage direct-to-implant mesh-assisted reconstruction in the UK, 22 which may be associated with higher complication rates than the traditional two-stage procedures 23 favoured in the US. 20 Risk factors for complications, including smoking and high BMI are consistent with those previously reported 24,25 and highlight the importance of careful patient selection if post-operative problems are to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of evidence on the impact of PMRT on prepectoral ADM‐implant reconstruction, with evidence to date comprising small retrospective case series with short‐term follow‐up. There are limited studies comparing clinical outcomes after immediate breast reconstruction using one‐stage direct to implant or two‐stage prepectoral ADM procedures with or without PMRT. There are provisional data suggesting potential tolerability of immediate prepectoral ADM‐implant breast reconstruction without excessive risks of complications in the short term.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 1 was a national practice questionnaire aiming to survey current practice, with phase 2 involving a multicentre prospective cohort study of patients undergoing IBBR to evaluate the clinical and patient-reported outcomes of these procedures. Phase 3 of the study used mixed-methods to investigate the acceptability of candidate trial designs generated in phase 1 [26,27] and phase 2 [9]. This included an electronic survey and qualitative interviews, which aimed to explore the acceptability of proposed RCT designs and possible barriers to RCT conduct in IBBR, from the perspective of those who would be potential trial recruiters.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%